PROTOCOL: Gender transformative approaches in agriculture for women's empowerment: A systematic review - Sabina Singh; Ashima Mohan; Ashrita Saran; Ranjitha Puskur; Avni Mishra; Linda Etale; Steven Michael Cole; Edoardo Masset; Hugh Sharma Waddington; Heather MacDonald; Howard White (Campbell Systematic Reviews, 2022)
Abstract This is the protocol for a Campbell systematic review. The objective of this systematic review is to assess the effectiveness of interventions with gender transformative approach (GTA) components in improving women's empowerment in low‐ and middle‐income countries, and to curate evidence on the mechanisms through which GTA works to improve women's empowerment in agriculture.